Local Government Discretion and Accountability : A Local Governance Framework - World Bank (Washington, DC, 2012)
This economic and sector work (ESW) report presents an analytical framework of local governance through the lens of accountability. It intends to establish a methodological basis for analyzing linkages between decentralization and accountability and is based on desk reviews and interviews. The main objective of this report is to present a coherent and comprehensive approach for decentralizing countries to achieve a high degree of local government discretion accompanied by robust accountability mechanisms. This report, which is a direct response to this growing interest, presents various social accountability mechanisms that could complement public sector accountability approaches. It also highlights the operational challenges the Bank's projects on local governance reform must often confront. Accordingly, the findings of this ESW provide, in one comprehensive framework, guidance on both macro policy-making and implementation of decentralization reforms.